Relationship among Perceived Stress, Academic Performance and Use of Energy Drinks: A Study on Universities' and Medical Students of Khyber Pakhtunkhwa Province of Pakistan - Hafeez, Shakir; Khan, Aman Ullah; Saeed, Bilal Bin; Javed, Yasir (International Review of Management and Marketing, 2016)
This study examined the relationship between perceived stress, academic performance participants and pattern of energy drink consumption in the context of higher education universities and medical students of Khyber Pakhtunkhwa province of Pakistan. Primary data was collected through self-designed Questionnaires including the Perceived Stress Scale and question about energy drink consumption, academic performance and demographics. Convenient sampling was used to select the universities and medical colleges of the province. To obtain the participants of study, random sampling technique was used. Consistent with the study hypotheses, the relationship existed between perceived stress and selected energy drink consumption items. Participants' perceived stress and academic performance was negatively correlated. The relationship between participants' perceived academic performance and energy drinks consumption was also found. It was found that medical students used more energy drinks as compare to non-medical students. There is a significant difference between male and female energy drink users. The participants who study in private sector institutions consume more drinks as compared to public sector students per month. More stress was found in female participants as compare to male. Comparatively medical students' stress level is high then non-medical students. Similarly stress level increases as one move from junior to senior level at his/her college or university. Keywords: Perceived stress; Academic performance; Energy drink consumption; Higher education institutes; Pakistan. JEL Classifications: C83, M10.